Do geography and institutions affect entrepreneurs' future business plans? Insights from Greece - Evangelos Rasvanis; Vassilis Tselios (Journal of Innovation and Entrepreneurship, 2023)
It is widely known that both geography and institutions determine the location of an investment. However, little is known about the impact of these factors on entrepreneurs' future business plans. Using a questionnaire survey, this paper examines whether the 'first-' and 'second-nature' geography and institutions affect the plans of entrepreneurs to expand or sell their businesses in Greece. The analysis shows that entrepreneurs intend to expand their businesses when the importance of the country's relative geographical location to the international market increases, but that of localisation economies decreases. There is also evidence that entrepreneurs aim to sell their businesses to domestic investors when sea access, the natural environment, the agglomeration economies, the location of Greece and the local governance are ideal for the business performance in the country.
Keywords: D02; M20; P28; R12; 650; Business expansion; Business selling; Geography; Greece; Institutions